A photograph of four orientalists (Bombay, 1885): knowledge production, religious identities, and the negotiation of invisible conflicts - Vicente, Filipa Lowndes (2012)
Abstract By analyzing the history of a photograph taken in a Bombay photo studio in 1885, this article explores notions of the production of knowledge on India and cultural dialogues, encounters, appropriations, and conflicts in colonial British India in the late nineteenth century. The photograph was taken after a Hindu religious ceremony in honour of the Italian Sanskritist Angelo de Gubernatis. Dressed as a Hindu Brahman, he is the only European photographed next to three Indian scholars, but what the image suggests of encounter and hybridity was challenged by the many written texts that reveal the conflicting dialogues that took place before and after the portrait was taken. Several factors were examined in order to decide who should and who should not be in the photograph: religion, cast, and even gender were successively discussed, before the category of “knowledge” became the bond that unified the four men who studied, taught, and wrote on India.